2016
DOI: 10.1172/jci83465
|View full text |Cite
|
Sign up to set email alerts
|

Targeting human melanoma neoantigens by T cell receptor gene therapy

Abstract: MethodsStatistics. Independent 2-sample t test was used to evaluate statistical differences between R24C/R24L and AAG/ELA data sets. P < 0.05 was considered significant, P < 0.01 highly significant.Study approval. All animal experiments were performed according to institutional and national guidelines, after approval by the responsible authority (Landesamt für Gesundheit und Soziales, Berlin). Blood collection from healthy human donors was done after prior informed consent. A complete, detailed description of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 30 publications
2
53
0
Order By: Relevance
“…Currently, there is no published data on neoantigen‐specific TCR‐engineered T‐cell therapy in humans. However, preclinical studies have shown encouraging results where neoantigen‐specific TCR‐engineered T cells are also effective for large‐sized solid tumors …”
Section: Neoantigen‐based Personalized Immunotherapymentioning
confidence: 99%
“…Currently, there is no published data on neoantigen‐specific TCR‐engineered T‐cell therapy in humans. However, preclinical studies have shown encouraging results where neoantigen‐specific TCR‐engineered T cells are also effective for large‐sized solid tumors …”
Section: Neoantigen‐based Personalized Immunotherapymentioning
confidence: 99%
“…Structural studies have revealed that two TCRs used in a clinical setting, DMF4 and DMF5, have to make structural compromises when interacting with the nonapeptide . In accordance, Blankenstein and colleagues recently showed that T cells, transduced with a clinically relevant TCR, induced rejection of tumors expressing the analog E L AGIGILTV, but not native AAGIGILTV, Melan A/MART‐1 epitope . Consequently, there is a need to understand the seemingly complex molecular rules that govern T‐cell antigen recognition in this system so that effective therapies can be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the neoantigen-targeting studies have been performed using melanoma samples, because melanoma has the highest somatic mutation burden among human cancers and hundreds of neoantigen candidates can be identified for each patient (34,(42)(43)(44)(45)(46). Only few studies have been performed in cancer types with a relatively lower number of somatic mutations, although a large body of evidence has suggested the importance of neoantigens.…”
Section: Discussionmentioning
confidence: 99%